A Newly Developed Sublingual Tonometric Method for the Evaluation of Tissue Perfusion and Its Validation In Vitro and in Healthy Persons In Vivo and the Results of the Measurements in COPD Patients - Zoltán Rózsavölgyi; Domokos Boda; Andrea Hajnal; Krisztina Boda; Attila Somfay (Critical Care Research and Practice)
Introduction. Since its first publication in the medical literature, an extremely large number of references have demonstrated that the tonometric measurement of tissue perfusion is a reliable indicator of the actual condition of critically ill patients. Later a new method was developed by the introduction of sublingual tonometry for the determination of tissue perfusion. In comparison with gastric tonometry, the new method was simpler and could even be used in awake patients. Unfortunately, at present, because of severe failures of manufacturing, the device is withdrawn from commerce. Materials and Methods. In this study, we present a new method using a newly developed tool for the PslCO2 measurement in sublingual tonometry as well as the data for its validation in vitro and in vivo and the results of 25 volunteers and 54 COPD patients belonging to different GOLD groups at their hospitalization due to the acute exacerbation of the disease but already in a stable condition at the time of the examination. Results and Conclusion. The results of the performed examinations showed that the method is suitable for monitoring the actual condition of the patients by mucosal perfusion tonometry in the sublingual region.